Sensor network scheduling for identification of spatially distributed processes - Uciński, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The work treats the problem of fault detection for processes described by partial differential equations as that of maximizing the power of a parametric hypothesis test which checks whether or not system parameters have nominal values. A simple node activation strategy is discussed for the design of a sensor network deployed in a spatial domain that is supposed to be used while detecting changes in the underlying parameters which govern the process evolution
Keywords: sensor network; parameter estimation; distributed parameter system; optimum experimental design; Fisher information matrix